Utilization of Design Application for Mufradat Class X MTS Baabusalam Learning - Wilda Fathia; Jeeny March; Puiry Sie (Yayasan Adra Karima Hubbi, 2022)
The quality of learning comes from learning that is designed and implemented by educators. An educator as the spearhead in the implementation of education is very influential in the learning process. Teaching and learning process activities One of the components that support learning so that it is carried out properly and regularly through learning media. Learning media as an intermediary between educators and students to understand learning more effectively and efficiently. The results of interviews with educators were very extraordinary at MTS Baabussalam during the Covid-19 pandemic, in the implementation of online learning, namely students were challenged to understand the teaching materials provided by educators in supporting the education of students, therefore students are required to learn through parental guidance at home. Learning media can be developed with interesting applications to support online learning. The approach between educators and students used in PKM program activities includes development training on learning media, one of which is using the Canva application which includes explanations about the Canva application, the history of the Canva application, the development of learning media for the Canva application, discussions and information exchange. Based on the results of training in making learning media, the Canva application greatly optimizes online learning for educators there. So, in pulling to the conclusion, the method that is my focus at this time is a qualitative method, which means research that focuses on analyzing events where the current research uses a theoretical basis that is factual in the field.